2021
DOI: 10.1007/978-3-030-86797-3_36
|View full text |Cite
|
Sign up to set email alerts
|

Organizing for Digital Innovation and Transformation: Bridging Between Organizational Resilience and Innovation Management

Abstract: Increased digitalization offers today's organizations novel opportunities to enhance value propositions for customers, but also poses significant challenges for traditional businesses. To navigate through the difficult process of digital transformation in this turbulent environment, organizations need to integrate successful innovation management practices and build organizational resilience.In this paper, we propose a conceptual framework that bridges between these two constructs: We describe innovation manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…First, a differentiation between affordances and their realization can be a valuable construct for decision-makers to analyze possibilities presented by smart technology. Further, consciously articulating expected outcomes of participating in smart service systems supports more efficient management of digital innovation within and beyond the organization (Heinz et al 2021;Nambisan et al 2017). Particularly, our understanding of smart service can inspire practitioners to rethink traditional roles of providers and consumers, as smart products and their connective capabilities allow novel value-creating actor constellations.…”
Section: Implications For Practicementioning
confidence: 99%
“…First, a differentiation between affordances and their realization can be a valuable construct for decision-makers to analyze possibilities presented by smart technology. Further, consciously articulating expected outcomes of participating in smart service systems supports more efficient management of digital innovation within and beyond the organization (Heinz et al 2021;Nambisan et al 2017). Particularly, our understanding of smart service can inspire practitioners to rethink traditional roles of providers and consumers, as smart products and their connective capabilities allow novel value-creating actor constellations.…”
Section: Implications For Practicementioning
confidence: 99%
“…Utilising broad stakeholder engagement, CSR gives rise to more flexibility when firms can access distinctive and diverse viewpoints and adjustments to external changes, fostering these firms' capacity to absorb shocks, which supports their organisational resilience [94,95]. However, Heinz et al (2021) emphasised that investment in CSR shapes deeper relationships with stakeholders in stable periods before shocks, providing firms with a greater opportunity to exhibit stability and recover more quickly after those shocks [22]. Studies have shown that companies that are more dedicated to social responsibility recover faster from economic crises [95,96].…”
Section: Cross-border Mandas Csr and Corporate Organisational Resiliencementioning
confidence: 99%
“…Companies with commendable corporate social responsibility (CSR) performance are likely to garner support from stakeholders, and research indicates that CSR can enhance the performance of cross-border M&As [21]. Firms that place a greater emphasis on social responsibility recover more swiftly during economic crises [22,23]. Additionally, a stronger market power aids companies in more effectively acquiring and integrating resources, thereby enhancing their ability to adapt to environmental changes [24].…”
Section: Introductionmentioning
confidence: 99%